BLOCKCHAIN IN HR: ENHANCING SECURITY AND TRANSPARENCY IN TALENT MANAGEMENT - Darodjat, Tubagus Achmad; Arapah, Sarah Nur (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This research investigates the impact of blockchain technology on security, efficiency, and transparency in talent management processes at PT Pertamina Gas - Head Office. Using a quantitative approach and structural equation modeling, data was collected from a random sample of 80 employees. The results reveal significant direct effects of blockchain implementation on data verification efficiency and transparency in talent management. Additionally, data verification efficiency was found to significantly influence transparency in talent management. However, the study did not find a significant direct effect of security measures on transparency when mediated by data verification efficiency. These findings underscore the importance of adopting innovative technologies such as blockchain to optimize HR processes and promote transparency in talent management. This research contributes to the growing body of literature on blockchain technology in HR and provides valuable insights for organizations seeking to enhance their talent management practices.